Sculpture at Goodwood 97/98 : British contemporary sculpture. - Elliott, Ann; Lynton, Norbert; Sculpture at Goodwood, Goodwood; Dyer, Angela (Goodwood : Sculpture at Goodwood, 1997)
Caro, Sir Anthony ; Pacheco, Ana Maria ; Maine, John ; Williams, Glynn ; Mach, David ; Allington, Edward ; Patel, Trupti ; Hamilton Finlay, Ian ; Chadwick, Lynn ; Mistry, Dhruva ; et al.
British contemporary sculpture at Goodwood 1997-98
kunstcatalogus